Beyond emissions reduction: A framework for integrating climate-change mitigation and sustainable development goals - Bioversity International and International Center for Tropical Agriculture; International Potato Center (2024)
Mitigating climate change extends beyond reducing greenhouse-gas emissions (GHGs). It also involves fostering sustainable economic development and enhancing well-being. This framework offers a comprehensive approach to integrating climate-change mitigation efforts with work to achieve the Sustainable Development Goals (SDGs) from a food systems perspective. It underscores the interconnection between environmental sustainability and socio-economic growth, emphasizing that reducing GHG emissions in food systems aligns with strategies to alleviate poverty, enhance food security, and protect ecosystems. By leveraging the co-benefits of climate action, this approach could drive progress on achieving the SDGs through attracting investment, building support, and informing strategic policy decisions.